ANALISIS TERHADAP NILAI KEBARUAN INVENSI VIRTUAL PRESENTER ARTIFICIAL INTELLIGENCE MILIK INEWS MEDIA GROUP: Analysis of the Novelty Value of the Artificial Intelligence Virtual Presenter Invention Owned by iNews Media Group - Monnalysa Julyan Chairul; Aline Gratika Nugrahani (AMICUS CURIAE, 2025)
The iNews Media Group, before submitting its invention to the Directorate General of Intellectual Property Rights, had already launched its invention, namely the Artificial Intelligence Virtual News Presenter in the form of a talk show titled "The Future of Artificial Intelligence Journalism" on August 3, 2023. The issue addressed by the author is whether the moment of the talk show titled "The Future of Artificial Intelligence Journalism," which simultaneously publicized iNews Media Group's Virtual Presenter invention of Artificial Intelligence, diminishes the novelty value of the invention. By using normative research methods, the author hopes to find an answer to the problem outlined. This research concludes that the publication of iNews Media Group's virtual presenter invention of Artificial Intelligence in the talk show falls under the exceptions category as stipulated in Law Number 13 of 2016 concerning Patents Article 6. However, because it has exceeded the tolerance period set by the inventor before patent application, it diminishes the novelty value. Therefore, the author recommends that before applying for a patent, iNews Media Group should first upgrade its Artificial Intelligence virtual presenter invention to maintain novelty value.